2015
DOI: 10.1007/s11136-015-1187-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in Parkinson’s: impact of ‘off’ time and stated treatment preferences

Abstract: 'On time' and predictability of 'off time' are highly valued by PwP. Due to substantial diurnal variation of Parkinson's symptoms, standard patient-reported outcome (PRO) assessments may not adequately capture the impact of 'off time' on HRQL and participation in daily activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Twenty‐two studies addressed the impact of “off” periods on patients (Table and Supporting Table 1). Eleven studies demonstrated an association between off periods and poorer HRQoL using generic or disease‐specific HRQoL scales . Motor symptoms described during off periods were diverse, including slow movements, decreased dexterity, tremor, stiffness, weakness, speech difficulty, balance difficulty, falls, and muscle cramps .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐two studies addressed the impact of “off” periods on patients (Table and Supporting Table 1). Eleven studies demonstrated an association between off periods and poorer HRQoL using generic or disease‐specific HRQoL scales . Motor symptoms described during off periods were diverse, including slow movements, decreased dexterity, tremor, stiffness, weakness, speech difficulty, balance difficulty, falls, and muscle cramps .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that 39‐item Parkinson's Disease Questionnaire (PDQ‐39) mobility scores were worse in patients with motor fluctuations . Motor limitations during off periods also have an impact on activities: The 10 most affected activities were, in order of frequency: dressing, hygiene, getting around the house, communicating effectively, walking short distances, looking after the home, moving in bed, cutting food, getting around public places, and writing . Not surprisingly, off periods were associated with poorer PDQ‐39 activities of daily living scores …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have derived utilities using the EQ-5D in multiple countries including Italy. [8][9][10] While these studies allow for comparisons across countries, the preferences and resulting utilities are not directly comparable because the EQ-5D values are based on patients' ratings of their own unique health, and there could be substantial variation in patient sample characteristics across countries. No studies were located that provide the opportunity for comparing utility values for the same health states in Italy and other countries.…”
Section: Introductionmentioning
confidence: 99%